Presentation and outcomes of adrenal ganglioneuromas: a cohort study and a systematic review of literature - Dages, Kelley N. (Clin Endocrinol (Oxf), 2021)
OBJECTIVE: To describe the presentation and outcomes of patients with adrenal ganglioneuromas (AGN). DESIGN: Single-center retrospective cohort study (January 1(st), 1995 to December 31(st), 2019) and systematic review of literature (January 1(st), 1980 to November 19(th), 2019). PATIENTS: Diagnosed with histologically confirmed AGN. MEASUREMENTS: Baseline clinical, imaging, and biochemical characteristics, recurrence rates, and mortality. Sub-group analysis was performed on tumors with histologic elements of ganglioneuroma and pheochromocytoma (i.e. composite tumors). RESULTS: The cohort study included 45 patients with AGN, 20 (44%) of which had composite tumors. Compared to pure AGN, patients with composite tumor were older (median age, 62.5 vs. 35 years, P <0.001), had smaller tumors (median size, 3.9 vs 5.7 cm, P = 0.016), and were discovered incidentally less frequently (65% vs 84%, P = 0.009). No recurrences or ganglioneuroma-specific mortality occurred during follow-up (range, 0-266 months). The systematic review included 14 additional studies and 421 patients. The mean age of diagnosis was 39 years and 47% were women. AGNs were discovered incidentally in 72% of patients, were predominantly unilateral (99%), had a mean diameter of 5.8 cm, and an unenhanced CT attenuation of −118-49 Hounsfield units (HU). On imaging, 69% of AGNs were homogenous, 41% demonstrated calcifications, and 40% were lobulated. CONCLUSIONS: AGNs are rare benign tumors that present with variable imaging features including large size, unenhanced CT attenuation >20 HU, calcifications, and lobulated shape. Imaging characteristics can assist in establishing a diagnosis and avoiding an unnecessary adrenalectomy. The association of pheochromocytomas with AGNs is frequent. Diagnosis should include biochemical testing.